Biodiversity, bathymetric distribution, and reproductive strategies of sea stars (Echinodermata: Asteroidea) in the Argentine Sea - Alarcon Saavedra, Ariana Belen (2025)
Sea stars (Echinodermata: Asteroidea) are widely distributed across all oceans, with numerous species inhabiting the Argentine Sea. This region is highly productive and sustains a rich diversity of marine invertebrates. The present work aimed to conduct a comprehensive bibliographic until 2024 review focusing on the biodiversity of Asteroidea in the different marine environments of Argentina and the reproductive strategies of sea stars inhabiting the Argentine Sea. This study focused on the geographic region from the Río de la Plata to the Burdwood Bank. We identified 105 species of sea stars, grouped into six orders, 19 families, and 60 genera. Valvatida and Forcipulatida were the most diverse orders. We noted a prevalence of sea stars in intermediate waters (50–500 m), being present across a wide range of temperatures. Regarding reproduction, our results showed that most of the brooding species were located exclusively in cold and intermediate waters, while broadcast spawner species exhibited a broad distribution from shallow to intermediate waters. This review highlights gaps in reproductive data for most species, as most studies in Argentina focus on identifying species from shallow rather than deeper waters. Enhancing sampling efforts and updating the biological information of these species will likely address these gaps in knowledge, especially in deeper areas where sampling is more challenging. Our results contribute to updating the knowledge of Asteroidea diversity in the Argentine Sea.